Digital media & society - Lindgren, Simon (SAGE, 2022)
"What does it mean to live in a digital society? Does social media empower political activism? How do we form and express our identity in a digital age? Do algorithms and search engine results have a social role? How have software and hardware transformed how we interact with each other? In the early 21st century, digital media and the social have become irreversibly intertwined. In this cutting-edge introduction, Simon Lindgren explores what it means to live in a digital society. With succinct explanations of the key concepts, debates and theories you need to know, this is a must-have resource for students exploring digital media, social media, media and society, data and society, and the internet."--Back cover.